2013
DOI: 10.1097/brs.0b013e318292aafa
|View full text |Cite
|
Sign up to set email alerts
|

Ossifications After Vertical Expandable Prosthetic Titanium Rib Treatment in Children With Thoracic Insufficiency Syndrome and Scoliosis

Abstract: 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
3
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 28 publications
2
25
3
2
Order By: Relevance
“…Two-thirds of our patients showed ossifications, which is a slightly higher rate than previously reported [14]. Half of those ossifications were situated around the anchors.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Two-thirds of our patients showed ossifications, which is a slightly higher rate than previously reported [14]. Half of those ossifications were situated around the anchors.…”
Section: Discussioncontrasting
confidence: 58%
“…However, there is a paucity of literature on those topics. Groenefeld and Hell recently claimed that the radiographic occurrence of ossification rose continuously up to 48 % at 53 months after the index procedure in a single-centre study of 57 VEPTR patients [14]. …”
Section: Introductionmentioning
confidence: 99%
“…Fusions of the ribs after VEPTR procedures have been documented and were found in our patient; this was likely the reason why the lengthening procedures failed to improve his thoracic volume. This finding is consistent with those of previous publications [12,13].…”
Section: Discussionsupporting
confidence: 83%
“…For example, the vertical expandable prosthetic titanium rib is indicated for treatment of thoracic insufficiency syndrome in skeletally immature patients. 26 Though subsequent follow-up studies suggested modest effect on lung function 27 and a possible increased risk of ossification, 28 the device has been valuable as a first step in spinal correction and improvement of quality of life for children with thoracic insufficiency syndrome and related disorders. 29 30 Other devices approved through the HDE pathway have been controversial.…”
Section: Performance Of Humanitarian Devicesmentioning
confidence: 99%